2018
DOI: 10.3389/fphys.2018.01550
|View full text |Cite
|
Sign up to set email alerts
|

PPIs Are Not Responsible for Elevating Cardiovascular Risk in Patients on Clopidogrel—A Systematic Review and Meta-Analysis

Abstract: Background: Clopidogrel and proton pump inhibitors (PPIs) are metabolized by cytochrome P450 enzymes. Contradictory results have been reported on possible complications of simultaneous PPI and clopidogrel use. Our aim was to investigate the clinical relevance of this debate with a systematic review and meta-analysis.Methods: The PubMed, Embase, and Cochrane Central Register of Controlled Trials electronic databases were searched for human studies [randomized controlled trials (RCTs) and observational studies] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 54 publications
(207 reference statements)
0
15
0
Order By: Relevance
“…Residual confounding may explain the wide‐ranging associations with PPI use observed both in the literature, where PPIs have been associated with over a dozen conditions, and in this study with cause‐specific mortality from a number of causes 1–9,38–40 . Notably, noninterventional research on the interaction between clopidogrel and PPIs similarly suffered from hard to account for confounding, and ultimately randomised trials suggested the harmful associations detected in many studies were not causal 13,41 …”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Residual confounding may explain the wide‐ranging associations with PPI use observed both in the literature, where PPIs have been associated with over a dozen conditions, and in this study with cause‐specific mortality from a number of causes 1–9,38–40 . Notably, noninterventional research on the interaction between clopidogrel and PPIs similarly suffered from hard to account for confounding, and ultimately randomised trials suggested the harmful associations detected in many studies were not causal 13,41 …”
Section: Discussionmentioning
confidence: 68%
“…[1][2][3][4][5][6][7][8][9][38][39][40] Notably, noninterventional research on the interaction between clopidogrel and PPIs similarly suffered from hard to account for confounding, and ultimately randomised trials suggested the harmful associations detected in many studies were not causal. 13,41 Our study has several strengths. It is the largest study to date to examine the association of PPI prescription with all-cause and causespecific mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing studies on the association between cardiovascular disorders and PPIs are conflicting. Several studies showed that PPIs were associated with an augmented risk of cardiovascular events (28-30), while others found no this association and supported the cardiovascular safety profile of PPIs (31)(32)(33).…”
Section: Discussionmentioning
confidence: 95%
“…Although most previous studies mainly focused on the effects of PPIs on CV outcomes in patients receiving clopidogrel (Kwok and Loke, 2010;Siller-Matula et al, 2010;Chen et al, 2012;Gerson et al, 2012;Kwok et al, 2013;Melloni et al, 2015;Sherwood et al, 2015;Serbin et al, 2016;Bundhun et al, 2017;Niu et al, 2017;Demcsák et al, 2018;Khan et al, 2018), the current study is the first comprehensive systematic review to examine the efficacy and safety profile of PPIs combined with DAPT in patients after PCI or ACS and is, to the best of our knowledge, the only study to evaluate the safety of PPIs with the concomitant use of other P2Y 12 inhibitors. This review of 22 studies with 6,930 patients from RCTs to 183,546 patients from observational studies showed that the use of PPIs probably reduced the risk of GI bleeding and UGI bleeding relative to no PPI use.…”
Section: Discussionmentioning
confidence: 99%